Violation of copyright in free access to information available on the Internet - Barrios Medina, Jorge Alexander; Tafur Mangada, Sacha Javier (DIXI, 2017)
Purpose: this article aims to analyze, from a legal perspective, the violation of copyright in relation to free access to information in the cyberspace in Colombia, and demonstrate how they are deliberately violated nowadays, even more so when Internet access is growing increasingly.Description: it is pointed out how information and communication technologies now allow access to the knowledge found in books, judgments, articles and, generally, different documents. It also broadens knowledge in various areas and fields of society.Point of view: the authors intend to examine the legal conditions of the right to free access to information in Colombia, and to identify legal mechanisms to protect such rights and how effective they are.Conclusions: the reader can get familiar with the poor practices that are usually followed in the preparation of academic and professional papers, which end up infringing copyright—in most cases, involuntarily—due to the use of inadequate techniques in the search for and processing of information.
Keywords: cyberspace; copy-pasting; copyright; free Internet access; plagiarism; ict